Pengenalan Dini Media Berbasis Layar sebagai Faktor Risiko Kegemukan pada Anak Prasekolah di Kota Yogyakarta - Neni Pangesti; I Made Alit Gunawan; Madarina Julia (JURNAL NUTRISIA, 2016)
Background: The prevalence of childhood obesity has increased over the years. It is caused by sedentary lifestyle that is often associated with early exposure to screen-based media. Early exposure refers to screen-based media introduction to children younger than 2 years old. This could lead to unhealthy habit until adolescent and adulthood. Screen exposure at an early age has also been associated with increased food intake. Objective: To analyze the effect of early screen-based media exposure to obesity risk among preschool children in the City of Yogyakarta. Method: This was a case-control study involving 101 obese and 101 non-obese preschool children aged 3-5 years who were enrolled at preschools in Yogyakarta. The school was selected using PPS (Probability Proportional to Size) method. The case and control were matched by age and gender. Obesity was defined by WHZ-score of > 2 SD. Data was analyzed using independent t-test, mc-Nemar test, spearman test, and conditional logistic regression. Result: Obese children were introduced to screen-based media 2 months earlier than their non-obese peers, the difference was however, not statistically significant. Screen-based media introduction was weakly corellated with parents’ income dan the amount of screen media at home. Early screen-based media exposure was not associated with childhood obesity (p>0, 05). Conclusion: Early screen-based media exposure did not increase the risk of obesity among preschool children in the City of Yogyakarta. Keyword: obesity, screen-based media, early exposure, preschool